The Role of Organizational Governance and Environmental Social Performance on Fraud Tendency - Anggraini, Melisa; Estrini, Dwi Hayu; Rahayu, Puspita Puji (Asia Pacific Fraud Journal, 2025)
This study aims to analyze the relationship between the independent board of commissioners, managerial ownership, and social environmental performance towards fraud. The sample of this research consists of 121 companies from the Asia Pacific Emerging Market and listed on Bloomberg’s database from 2016 to 2022. The multiple regression analysis is conducted to examine the relationship between the independent board of commissioners, managerial ownership, and social environmental performance towards fraud. The findings of this study showed that independent boards of commissioners and managerial ownership don’t affect fraud, but social-environmental performance does. This study contributes to the existing literature by providing evidence on the global market and how the elements of corporate governance and social environmental performance can affect fraud. This study also supports the stakeholder theory, which proposes that when a company makes social environmental performance a strategic orientation of the company, then fraud can be minimized because the company is not just responsible for itself but also for the other stakeholders.